Evaluation of Microstructure Formation and Phase Equilibria for Thermoelectric β-FeSi2 Composite Alloys. (30th January 2017) - Kimura, Yoshisato; Otani, Hiroaki; Mori, Ayaka; Chai, Yaw-Wang
ABSTRACT: Thermoelectric composite alloys consisting of the β-FeSi2 matrix and SiO2 particles dispersion were fabricated by a so-called combined reactions sintering process using reduction and oxidation reactions between eutectoid Si decomposed from α-Fe2 Si5 and added Fe-oxide powder. Typical microstructure may include some of residual eutectoid Si particles, intermediate product Fe2 SiO4 particles, and/or remaining reduced Fe particles depending on the composite alloy compositions and the process conditions. Partitioning of doping element, n-type Co or p-type Mn, during the process plays an important role to control the optimum carrier concentration of the composite alloys. Thermal conductivity can be reduced, as expected, by the dispersion of SiO2 particles. The solubility of doping elements, Co, Mn, Al, and Ru was evaluated in α-Fe2 Si5 at 1373 K and in β-FeSi2 at 1073 K being based on the isotherm determination. It is suggested that suitable dopants for the present process are n-type Co and p-type Mn, since they have sufficiently large solubility around 10 at% in both α-Fe2 Si5 and β-FeSi2 phases.